Moisture transport across porcine skin: experiments and implementation of diffusion-based models. (17th November 2010) - Kar, Saptarshi; Chen, Xiao Dong
In this paper, the mechanism of moisture transport across porcine skin has been investigated. Such work has implications on transdermal delivery of hydrophilic drugs. Past studies conducted in this area mostly relied on studying the process of moisture absorption. Mathematical models proposed for this transport process have been very basic. In this study, desorption as opposed to absorption has been used as the experimental approach for studying moisture transport. Low temperature convective drying experiments of the skin samples were conducted. Prior to the drying experiments, the skin samples were pre-treated by soaking in water at different temperatures for one hour. It was observed that the pre-treatment method had an effect on the drying rate. The mathematical models implemented were similar to the Fickian diffusion equation. The study yielded useful findings, which would interest researchers working in the area of drug delivery, toxicology and thermal burn analysis as well as those involved in the area of passive moisture transport through porous materials notably encountered in process engineering applications such as leather drying.